2013
DOI: 10.1007/s10456-013-9403-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor gangliosides accelerate murine tumor angiogenesis

Abstract: Tumor cells shed gangliosides and populate their microenvironment with these biologically active membrane glycosphingolipids. In vitro, ganglioside enrichment amplifies receptor tyrosine kinase signaling and activation of vascular endothelial cells. However, a long-standing question is whether in the actual microenvironment of a neoplasm, in vivo, tumor cell ganglioside shedding stimulates angiogenesis. Here we tested the hypothesis that tumor gangliosides have a critical proangiogenic role in vivo using novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…This result corresponds with the fact that B4GALNT1 is a clinical marker for advanced melanoma 59 . Liu Y et al revealed that gangliosides accelerate tumor angiogenesis in murine cells and demonstrated that GM2/GD2-negative cells formed much smaller tumors, using GM3 synthase and GM2 synthase double knockout low ganglioside tumor model 60 . We assessed murine-CD31 expression in the tumors derived from GM2/GD2-positive cell by immunofluorescence staining and observed that B4GALNT1-overexpressing clones induced many CD31 positive endothelial cells and well-developed vessels.…”
Section: Symbolmentioning
confidence: 99%
See 1 more Smart Citation
“…This result corresponds with the fact that B4GALNT1 is a clinical marker for advanced melanoma 59 . Liu Y et al revealed that gangliosides accelerate tumor angiogenesis in murine cells and demonstrated that GM2/GD2-negative cells formed much smaller tumors, using GM3 synthase and GM2 synthase double knockout low ganglioside tumor model 60 . We assessed murine-CD31 expression in the tumors derived from GM2/GD2-positive cell by immunofluorescence staining and observed that B4GALNT1-overexpressing clones induced many CD31 positive endothelial cells and well-developed vessels.…”
Section: Symbolmentioning
confidence: 99%
“…Lang Z et al found that the enrichment of human umbilical vein endothelial cell (HUVEC) membranes with ganglioside results in amplified VEGF-induced signaling that is important for angiogenesis, and concluded that ganglioside enhances VEGF-induced endothelial cell proliferation 61 . Liu Y et al reported that reduction of gangliosides depleted vascularization, while addition of wild type gangliosides restored angiogenesis of ganglioside-poor tumor 60 . To clarify how gangliosides induce blood vessels, we assessed the relations of GM2/GD2 and VEGF.…”
Section: Symbolmentioning
confidence: 99%
“…The deficit of infiltrating MDSC in ganglioside-poor DKO tumors may also in part explain the negative impact that the absence of gangliosides has on another process important to tumor growth, angiogenesis (30). In this case, it is tempting to speculate that since MDSC directly promote tumor angiogenesis (31) and the poorly vascularized, poorly growing ganglioside-poor DKO tumors have greatly reduced angiogenesis (30), tumor accumulation of MDSC (dependent on the presence of tumor gangliosides) is an “effector mechanism” that is at least in part also responsible for ganglioside enhancement of tumor angiogenesis. The ultimate outgrowth…”
Section: Resultsmentioning
confidence: 99%
“…Whereas a concentration-dependent effect can be suggested for the anti-angiogenic action of glucosylsphingosine, this same relationship does not hold true for the complex gangliosides, as the pro-angiogenic compounds G M1 , G M2 , G D1a and G D3 [4,[46][47][48][49][50] dominate by volume over gangliosides with suggested anti-angiogenic actions, most particularly G M3 [6,46,51,52]. This might be explained by a dominant pathogenic effect of glucosylsphingosine -in line with the long-held, although incomplete, 'psychosine hypothesis' of pathogenicity [53].…”
Section: Discussionmentioning
confidence: 99%